The many mysteries of Homo naledi - Chris Stringer (eLife, 2015)
More than 1500 fossils from the Rising Star cave system in South Africa have been assigned to a new human species, Homo naledi, which displays a unique combination of primitive and derived traits throughout the skeleton.